The Influence of Trend Fashion, Influencer Marketing, Brand Image, and Online Customer Reviews on Fashion Product Purchasing Decision - Fauziyah Nur Jamal; Bagus Gumelar; Ahmad Rizal Solihudin; Riza Muzianita; Wafrotur Rohmah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The most important thing in marketing activities is the purchasing decision, after consumers consider many factors and the final decision is to make a purchase. Some factors that can influence purchasing decisions on fashion products are fashion trends, influencer marketing, brand image and online customer reviews. The purpose of this study is to determine the effect of fashion trends, influencer marketing, brand image and online customer reviews on purchasing decisions for fashion products on e-commerce shopee. The number of samples in this study was 136 respondents, some of all e-commerce users in Indonesia. This study uses a quantitative approach. Sampling uses non-probability sampling techniques and purposive sampling methods. Data analysis uses SEM-PLS 4.0. The results of this study showed that fashion trends have a positive and significant effect on purchasing decisions. Influencer marketing has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Online customer reviews have a positive and significant effect on purchasing decisions. This study is expected to be able to increase knowledge for companies in implementing marketing strategies.